Design, synthesis and bioactivity evaluation of a series of quinazolinone derivatives as potent PI3Kγ antagonist. (15th April 2023) - Liang, Yuqing; Zheng, Yanjun; Yang, Junjie; Ke, Jiahua; Cheng, Kui
Graphical abstract: Abstract: Targeting PI3Kγ would be a useful strategy for treating inflammatory and cancer diseases. However, the development of selective inhibitors of PI3Kγ is very challenging due to the high structural and sequence homology with other PI3K isoforms. A series of quinazolinone derivatives were designed, synthesized and biologically evaluated as PI3Kγ-selective inhibitors. Among all the 28 compounds, compound 9b was found to be the most potent selective inhibitor with IC50 values of 13.11 nM against PI3Kγ kinase. Additionally, compound 9b could generate toxicity on leukemia cells in a panel of 12 different of cancer cell lines with the IC50 value of 2.41 ± 0.11 μM on Jurkat cell. Preliminary mechanism studies indicated that compound 9b through inhibit the activity of PI3K-AKT in human and murine leukemia cells, and activated phosphorylated p38 and phosphorylated ERK presented potent antiproliferative activity, which provided a potent small molecule for further cancer therapy.